Inovace marketingové strategie vybrané sportovní akce - Cupalová, Nicol (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Bakalářská práce se zabývá inovací marketingové strategie pro vybranou sportovní akci GALA DANCE STARLET 2014. Teoretická východiska práce se zaměřují na obecnou teorii marketingu, specifika a trendy sportovního marketingu. Analýza současného stavu podrobně popisuje celou akci pro využití na následné návrhy vlastních inovací s výsledky ankety.

The Bachelor thesis deals with innovation of marketing strategies of selected sporting events GALA DNACE STARLET 2014. The theoretical basis of the work focus on the general theory of marketing, specifics and trends of sports marketing. Analysis of the current state detailing the entire event for use on subsequent proposals of its own innovations with the results of the questionnaire.
Innovation Marketing Strategy of Selected Sporting Events
Keywords: sportovní marketing; marketingové trendy; sportovní tanec; GALA DANCE; inovace; sports marketing; marketing trends; ballroom dancing; GALA DANCE; innovation